Marcas surdas: escola, família, associação, comunidade, e universidade constituindo cultura e diferença surda - Chiella, Vânia Elisabeth (Universidade do Vale do Rio do Sinos, 2007)
The present research aims at both analyzing and problematizing deaf cultural markers. In order to do that, I have selected doctorate theses, master’s dissertations, and dissertation projects written in Portuguese by deaf subjects who have struggled for the deaf policy. The selection of the research materials has been based on the observation that deaf individuals bring life histories to their writings, which enable us to see some elements that are characteristic of the deaf community. Grounded on the Cultural Studies, with post-structuralist inspiration, as well as on Deaf Studies, I have been able to define some conceptual tools that operate in the deaf narratives about the self. In such narratives, school, community, association, family, and university have emerged as places for the constitution of deaf marks. The cultural marks that I have seen as constituting the deaf difference from the analysis category called space/place are deafness, struggle, nostalgia of being deaf, presentiality, deaf temporality,
Keywords: análise de texto; cultura surda; linguagem; marcadores culturais; narrativas surdas; surdos; estudo cultural; Ciências Humanas